DIGITAL MANUFACTURING MODEL FOR REMOTELY OPERATED VEHICLE (ROV) IN INDONESIA: A CONCEPT STUDY - Artaraharja, Yoseph Daniswara; Widjaja, Sjarief; Hermawan, Yuda Apri (Journal of Marine-Earth Science and Technology, 2023)
Industrial revolution 4.0 era represents a paradigm shift in manufacturing and technology, which is characterized by an integrated and interconnected system to support the operation of an industry. Many countries contributed to this era, including Indonesia. As a maritime country, maritime-related products have the potential to be offered. Remotely operated vehicles (ROV) is a form of digitalization product that is frequently used to support the operation of the maritime industry. Therefore, ROV is manufactured locally to provide easier access to industries demanding ROV. Digital manufacturing for ROV can bring further contributions towards industrial revolution 4.0, which involves the usage of digital technologies such as computer-aided design and manufacturing (CAD/CAM), internet of things (IoT), artificial intelligence (AI), and robotics to create an integrated manufacturing system. Furthermore, digital manufacturing information system provides real-time information during the manufacturing process. According to this study, digital manufacturing can significantly improve the efficiency and integration in manufacturing the ROV.